Efektivitas Nutrisi Medik Berbahan Aktif Mengkudu dan Apel Manalagi Terhadap Penurunan Kadar Glukosa Darah: Efficacy of Medical Nutrition using Active compounds of Noni and Manalagi Apples to Reduce Blood Glucose Levels - Selfia Selfia; Muhammad Faisal; Niken Indriyanti (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Noni (Morinda citrifolia L.) contains saponin compounds that work to stimulate insulin secretion from ?-pancreatic cells and manalagi apples (Malus sylvestris Mill.) contain pectin which functions to delay the emptying of food in the stomach, bind fatty acids and reduce macronutrient absorption which can cause decreased blood glucose levels. This study aims to prove that medical nutrition with active ingredients of noni and manalagi apples has effectiveness in reducing blood glucose levels, prove that doses of medical nutrition with active ingredients of noni and manalagi apple are effective for lowering blood glucose levels and prove a decrease in blood glucose levels 30 minutes after treatment. The research method used is quasi-experimental with the measurement of blood glucose levels pre-test and post-test using human test subjects. The research ethics protocol has been obtained with No. 71/KEPK FFUNMUL/EC/EXE/08/2021 from KEPK FF UNMUL. The results showed that the administration of medical nutrition with a dose of 126 g of noni and 200 g of manalagi apple and a dose of 63 g of noni and 100 g of manalagi apple was effective in reducing blood glucose levels, with an average decrease in blood glucose levels of 9,60 ± 7,47 mg/dL and 6,40 ± 3,91 mg/dL. It can be concluded that the most effective dose to reduce blood glucose levels is medical nutrition with a dose of 126 g of noni and 200 g of manalagi apples.